The sociology of technology before the turn to technology. (November 2016) - Gunderson, Ryan
Abstract: This project recommences an underdeveloped conversation between the sociology of technology and classical sociology. There was a vibrant and consistent interest in technology among sociology's founders between Marx and Ogburn and revisiting this tradition is beneficial for contemporary sociological studies of technology. In addition to functioning as exemplars of excellence for the sociology of technology, classical sociology provides distinctive and important considerations and contributions, including: the potential benefits of borrowing technology (Veblen), the ecological influences on technological development and use (Cooley), the impact of technology on science (Mauss), and the rationalization of technology (Weber). Most importantly, classical sociology offers partial though unique frameworks for examining technology in society and vice versa, frameworks that are novel precisely because they are out of sync with recent trends. Highlights: There is a long and fruitful history of sociological investigations of technology. Classical sociology provides distinctive and important contributions. Revisiting this tradition is beneficial for contemporary technology studies.